מסכת המוות של פול דה מאן - גינזבורג, שי (מכאן, 2016)
This essay presents a close reading of Paul de Man’s seminal essay, Autobiography as Defacement. It seeks to uncover the unsettling effect de Man finds in autobiography by paying close attention to the images of the suffering human body and its death, which are central to his essay. The current article contends that for de Man, the autobiography manifests the human condition,  which he sees as a radical dualism of mind and body. Indeed, the human condition is characterized by the inability of the mind to account for the suffering of the body, and beyond that, by an inability to articulate that suffering in language.